Diffusion curves with diffusion coefficients - Hongwei Lin; Jingning Zhang; Chenkai Xu (Computational Visual Media, 2018)
Abstract Diffusion curves can be used to generate vector graphics images with smooth variation by solving Poisson equations. However, using the classical diffusion curve model, it is difficult to ensure that the generated diffusion image satisfies desired constraints. In this paper, we develop a model for producing a diffusion image by solving a diffusion equation with diffusion coefficients, in which color layers and coefficient layers are introduced to facilitate the generation of the diffusion image. Doing so allows us to impose various constraints on the diffusion image, such as diffusion strength, diffusion direction, diffusion points, etc., in a unified computational framework. Various examples are presented in this paper to illustrate the capabilities of our model.